Comparative Analysis of Cx31 and Cx43 in Differentiation-Competent Rodent Keratinocytes - Akina Au; Qing Shao; Kyra K. White; Sergiu A. Lucaciu; Jessica L. Esseltine; Kevin Barr; Dale W. Laird (Biomolecules, 2020)
When considering connexin expression and regulation, the epidermis of the skin is one of the most complex tissues found in mammals even though it largely contains a single cell type, the keratinocyte. In the rodent epidermis, up to 9 connexin family members have been detected at the mRNA level. Many of these connexins are temporally and spatially regulated in coordination with keratinocyte progenitor cell differentiation and migration from the stratum basale to form the stratum spinosum and stratum granulosum layers before finally forming the stratum corneum. Cx43 is the principal connexin found in basal keratinocytes and to a lesser degree found in keratinocytes that have begun to differentiate where Cx26, Cx30 and Cx31 become prevalent. Here we show that the CRISPR-Cas9 ablation of Cx43 reduces overall gap junction coupling in monolayer cultures of rat epidermal keratinocytes (REKs) and dysregulates the differentiation of REKs when grown in organotypic cultures. Natively found in differentiated keratinocytes, Cx31 readily assembles into gap junctions when expressed in REKs where it can extensively co-assemble into the same gap junctions with co-expressed Cx30. Time-lapse imaging indicated that many Cx31 gap junctions are mobile within the plasma membrane undergoing both fusion and fission events. Finally, the persistence of pre-existing Cx31 gap junctions in the presence of the protein trafficking blocker, brefeldin A, is longer than that found for Cx43 gap junctions indicating that it has a distinctly different life expectancy in REKs. Collectively, this study highlights the importance of Cx43 in rodent keratinocyte differentiation and suggests that Cx31 acquires life-cycle properties that are distinct from Cx43.